DETERMINANTS OF RENTAL INCOME TAX COMPLIANCE AMONG RENT INCOME EARNERS IN GHANA - Ayariga, Charles; Blay, Marshall Wellington; Musah, Alhassan; Monira, Nurjahan Akter (International Journal of Accounting & Finance Review, 2024)
Rent tax compliance has been a major problem in many developing countries but Ghana's case is worse as successive governments have failed to enhance rent tax compliance. Rental taxation is economically significant, yet a substantial portion of landlords and developers fail to meet their tax obligations. This issue is particularly prevalent in Ghana, where rental income tax compliance remains low despite its potential to contribute significantly to national revenue. This study focuses on identifying the factors influencing compliance, specifically examining the roles of compliance costs, tax rate/structure, tax knowledge and education, and fines and penalties.  Utilizing a quantitative research design, data was gathered from 260 rent income earners through questionnaires, out of a targeted sample size of 272. Descriptive statistics and a multiple regression model were employed to analyse the data and identify relationships between the studied variables and rental income tax compliance. The analysis identified a noteworthy positive association between the cost of compliance and tax rate/structure and rental income tax compliance. The results imply that tax compliance costs and the tax rate are significant determinants of rent tax compliance in Ghana. Conversely, tax knowledge and education, as well as fines and penalties, showed an insignificant negative effect on compliance. The study results imply that a proactive approach to reducing compliance costs and enhancing tax structures positively influences compliance among rental income earners. Educational efforts and penalties, however, may require alternative strategies to be effective. JEL Classification Codes: H24, H25, H26, K42.